Integrated Metaphorming Learning Model of 21st Century Skills to Increase Student Creativity - Zuhra, Fatma; Nurhayati; Jasmaniah; Karim, Asrul (MIMBAR PGSD Undiksha, 2023)
Based on PISA research, current learning has yet to be able to develop student creativity. Creativity is an ability that reflects fluency, flexibility in thinking, and the ability to develop, enrich, and detail quality ideas to solve problems. This research was conducted to analyze the increase in student creativity through an integrated Metaphorming learning model for 21st century skills. This research used a quantitative approach, a quasi-experimental type, and a Nonequivalent Control Group Design. The data collection method uses tests. The data collection instrument uses test questions. The sample was 30 students from Unit D as the control class and Unit E with 32 students as the experimental class who were selected using purposive sampling. The data analysis technique uses gain index calculations (N-Gain). The research results show that the Metaphorming learning model integrated with 21st century skills can increase student creativity. However, learning outcomes are similar between students taught with the integrated Metaphorming learning model of the 21st century and with the integration of 21st-century skills. Hypothesis testing shows that Creativity only influences a 25% increase in student learning outcomes; the rest is influenced by factors not measured in this research. It was concluded that the Metaphorming learning model integrated with 21st century skills positively impacted student creativity.